Improving Student Career Readiness Through Transferable Skills-Based Guidance Modules - Ahmad Rofi Suryahadikusumah; Fauzan Nazil Ramadhan (ProGCouns: Journal of Professionals in Guidance and Counseling, 2025)
Graduates of Islamic boarding schools often face obstacles in obtaining jobs, and only a small number enter the professional field. The study aims to improve Salafi Islamic boarding school students' career readiness through a transferable skills-based career guidance module that equips them with abilities and knowledge applicable across various jobs and career levels, aligned with career development in the era of disruption. The research method used a quasi-experiment. The research sample consisted of 25 people, selected purposively from fifth- and 7th-semester students at Islamic boarding schools who were willing to participate in a series of research activities. Data collection used Transferable Skills Analysis (TSA) and Student Career Readiness Index (SCRI). The results of the study showed that the transferable skills-based career guidance module was effective in improving the career readiness of Salafi Islamic boarding school students, as indicated by a Z value of 4.380 in the Wilcoxon Test, with a significance (2-tailed) of 0.000. The most significant changes in career readiness were the dimensions of career management and seeking information and assistance.